Individual and Collective Choice and Social Welfare: Essays in Honor of Nick Baigent - Binder, C (Springer, 2015)
The papers in this volume explore various issues relating to theories of individual and collective choice, and theories of social welfare. The topics include individual and collective rationality, motivation and intention in economics, coercion, public goods, climate change, and voting theory. The book offers an excellent overview over latest research in these fields.